Future extreme climate changes linked to global warming intensity - Wang, Xiaoxin; Jiang, Dabang; Lang, Xianmei (Science bulletin, 2017)
Based on the Coupled Model Intercomparison Project Phase 5 （CMIP5） daily dataset, we investigate changes of the terrestrial extreme climates given that the global mean temperature increases persistently under the Representative Concentration Pathways 8.5 （RCP8.5） scenario, Compared to preindustria/conditions, more statistically significant extreme temperatures, precipitations, and dry spells are expected in the 21st century. Cold extremes decrease and warm extremes increase in a warmer world, and cold extremes tend to be more sensitive to global warming than the warm ones. When the global mean temperature increases, cold nights, cold days, and warm nights all display nonlinear relationships with it, such as the weakening of the link projected after 3 ℃ global warming, while the other indices generally exhibit differently, with linear relationships, Additionally, the relative changes in the indices related to extreme precipitation show significantly consistent linear changes with the global warming magnitude. Compared with the precipitation extremes, changes in temperature extremes are more strongly related to the global mean temperature changes. For the projection of the extreme precipitation changes, models show higher uncertainty than that in extreme temperature changes, and the uncertainty for the precipitation extremes becomes more remarkable when the global warming exceeds 5℃.